Macroporous monolithic polymers: preparation and applications - Arrua, Ruben Dario (2009)
In the last years, macroporous monolithic materials have been introduced as a new and useful generation of polymers used in different fields. These polymers may be prepared in a simple way from a homogenous mixture into a mold and contain large interconnected pores or channels allowing for high flow rates at moderate pressures. Due to their porous characteristics, they could be used in different processes, such as stationary phases for different types of chromatography, high-throughput bioreactors and in microfluidic chip applications. This review reports the contributions of several groups working in the preparation of different macroporous monoliths and their modification by immobilization of specific ligands on the products for specific purposes.